Ultrasonography-guided oocyte recovery in owl monkeys (aotus azarai infulatus) - Rech, Fernanda; Souto, Marcella Pinheiro; Oliveira, Jimmy Wiggley Moura; da Silva, Sandy Kelly Souza Marques; Viau Furtado, Priscila; Imbeloni, Aline Amaral; Teixeira, Pedro Paulo Maia; de Lima, Julianne Silva; Vicente, Wilter Ricardo Russiano [UNESP]; Coutinho, Leandro Nassar (Wiley, 2021)
The study evaluated an echo-guided oocyte recovery technique in owl monkeys. Twelve females were selected for the transabdominal ovum retrieval technique. This procedure collected twenty-six follicles, of which nine oocytes were recovered, without harm to the animals. The technique is feasible and is a minimally invasive protocol for neotropical primates.
Keywords: Aotidae; echo-guided; neotropical primates; oocyte retrieval